PENGARUH PELAYANAN PT. TELKOM SPEEDY TERHADAP KEPUASAN KONSUMEN DI KECAMATAN PONTIANAK SELATAN - E.01109027, Sugianto (FISIP Universitas Tanjungpura, 2014)
Factors that affect customer satisfaction is a good service to consumers with the level of customer satisfaction are met in their use, so how should PT.Telkom can improve a customer satisfaction rate of the provision of services Telkom Speedy. This study aims to determine whether there is a significant effect or not, between PT Telkom Speedy service on customer satisfaction in the District of South Pontianak. The investigations on this, see the level of customer satisfaction based on Display, reliability, responsiveness, assurance, empathy. The data collection instruments in the form of a questionnaire that has been validated and statistically terealibilitasi. While customer satisfaction seen in the results of the test sample of respondents who are satisfied will be a service PT.Telkom validity and reliability. This study uses quantitative methods associative type of research is research that analyzes the causal relationship between the variables with other variables or how a variable affects the other variable. The population in this study was 171. Amount of 30% of samples taken at random from the total population, so that the total sample of 120 consumers Speedy service users. The results of the writing of this article is classified in the level of consumer satisfaction criteria are quite satisfactory. Service quality to customer satisfaction is affected by 45.4%, and 54.6% are influenced by other factors. Based on calculations using the statistical analysis of the product moment formula, declare that there is a significant relationship between the level of customer satisfaction of service users in Sub Speedy South Pontianak.Suggestion of this paper is PT.Telkom Speedy PT.Telkom must convince customers that Speedy is the best choice as their internet service provider, through the high quality services that Speedy can meet the high expectations of customers in the District of South Pontianak. Therefore, researchers suggest that Speedy can be more focused and consistent in providing the best service over internet services they offer, so it makes Speedy primary choice for Internet users as an internet service provider in the District of South Pontianak.Â Keywords : Service Quality, Customer Satisfaction, PT.Telkom Pontianak